RICE TRADERS' STRATEGIES IN INCREASING SALES TURNOVER IN WANCI SUBDISTRICT, WAKATOBI REGENCY ACCORDING TO SHARIA ECONOMIC PRINCIPLES - Wanci, Yeni; Sari, Sarni Handayani Puspita (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to determine and analyze the effect of price and rice promotion strategy on purchasing decisions with rice customer satisfaction in increasing turnover in Wanci Village, Wakatobi Regency according to Islamic Economics directly or indirectly. The study uses a descriptive associative approach. The population in this study includes several samples of traders in Wanci Village. The number of samples is set at 10 respondents. Data collection techniques use questionnaires and interviews. Data analysis techniques use a quantitative approach. The results of the study indicate that directly, price and promotion each have a significant effect on purchasing decisions. Price and promotion each have a significant effect on customer satisfaction.